Pengembangan Wisata Masjid Baitussalam Nyak Sandang Sebagai Icon Wisata Religi di Aceh Jaya - Husnul Arifah; Hari Santoso; Iqbal Muttaqin; Intan Karnia Sari; Fatimah Zahara; Egi Liyana Budi Pratama; Moza Fitria; Ahmad Maulana; Asyrof Kholil; Muhammad Azan; Apria Rina Ridara; Mega Anjarwati; Andre Yubentro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research is used as a form of student service for the Malay Column III Real Work Lecture to the people of Aceh Jaya (Lamno) Gampong Lhuet. Religious tourism is the application of the concept of halal tourism which has the aim of meeting human spiritual needs in strengthening faith by visiting places that have religious values. gampong lhuet has great potential and opportunities in developing religious tourism, namely the Baitussalam Nyak Sandang Mosque as its icon. Nyak clothes, who is he? Maybe many do not know who he is. And thanks to his request, the President of the Republic of Indonesia, Joko Widodo, built the Baitussalam mosque for him. The method used in this study is a descriptive qualitative method to describe the potential for religious tourism in the region, with primary data sources and secondary data sources. There are several things that must be considered in the development of this religious tourism, namely the potential, opportunities, and challenges in development. And also have to know what strategy to use. The strategy used in this study is to make this religious tourism icon viral on all social media so that it can be famous and known to many people. The strategy has succeeded in attracting visitors coming from various regions.